Peran Pembelajaran Bahasa dan Sastra Indonesia dalam Membentuk Karakter Pada Era Vuca - Syamsuri, Andi Sukri; Bur, Eka Yulianti (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the Role of Learning the Indonesian Language and Literature in Character Building during the VUCA Era. In carrying out this research, the authors used a descriptive-qualitative approach. The source of the data in this study was the Class X High School/Vocational High School Indonesian Language Teaching Material Books published by the Ministry of Education, Culture, Research and Technology, the Agency for Research and Development and Books, and the Center for Curriculum and Books. The number of pages in this book consists of 248 pages. The data in this study are in the form of clauses, sentences, and images containing 18 characters set by the Ministry of National Education. The results showed that: 1) The character of creativity is described through a text entitled "Presenting Observation Reports in the Form of a Scrapbook", 2) The character of Responsibility is described through a text entitled "Presenting Observation Reports", 3) the character of Love for Peace is described through the text "Expressing Criticism Through a Smile", 4) the character of Discipline is described through the text "Cellphone Addict" 5) The Character of Concern for the Environment is described through the text "Use Plastic Substitutes From Now On", and finally 6) The Character of Social Care is described through the text "Internet Behavior Bullying”. AbstrakPenelitian ini bertujuan untuk mendeskripsikan Peran Pembelajaran Bahasa dan Sastra Indonesia dalam Membentuk Karakter pada Era VUCA. Dalam melaksanakan penelitian ini, penulis menggunakan pendekatan deskriptif-kualitatif. Sumber data dalam penelitian ini, yaitu Buku Bahan Ajar Bahasa Indonesia SMA/SMK Kelas X yang diterbitkan oleh Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi, Badan Penelitian dan Pengembangan dan Perbukuan, Pusat Kurikulum dan Perbukuan. Jumlah  halaman dalam buku ini terdiri atas 248 halaman. Data dalam penelitian ini berupa klausa, kalimat, dan gambar yang memuat 18 karakter  yang ditetapkan oleh Kemendiknas. Hasil penelitian menunjukkan bahwa: 1) Karakter kreativitas digambarkan melalui teks yang berjudul “Menyajikan Laporan Hasil Observasi dalam Bentuk Buku Tempel”,  2) Karakter  tanggung jawab digambarkan melalui teks yang berjudul “Mempresentasikan Laporan Hasil Observasi”,  3) karakter cinta damai digambarkan melalu teks “Mengungkapkan Kritik Lewat Senyuman”, 4)  karakter disiplin digambarkan melalui teks “Ponsel Pecandu “ 5)  Karakter Peduli Lingkungan digambarkan melalui teks “Gunakan Barang-Barang pengganti Plastik Mulai Sekarang”, dan terakhir 6) Karakter peduli sosial digambarkan melalui teks“Internet Perilaku Perundungan”.